Effects of using blogs on writing performance of students in a secondary school, Kuantan, Malaysia - Subramaniam, Sri Shangari (2015)
The present study aims at answering two research questions. The first research question is if there is a significant improvement in the writing performance of secondary school students in using weblogs in the English classroom. Students’ writing performance is evaluated based on five components from the Jacob’s ESL Profile (1981). These components include content, organization, sentence construction, voice as well as mechanics and proofreading. In addition, it also aims at answering the second research question which is to identify secondary school students’ perception of using weblogs in their English classroom to help them write better. The participants in this study comprised of 17 form four students from a secondary school in Kuantan, Pahang. Data was collected by comparing the scores for their first three blog entries and their last three blog entries. The evaluation was done by two external raters using the ESL Profile. A Pearson’s product-moment correlation was performed to determine the coefficient of interrater reliability on the first three blog entries and the last three blog entries. The result showed a positively strong and significant relationship. A mean mastery score is provided for each component of the evaluation (content, organization,sentence construction, voice and mechanics and proofreading). A t-test was then conducted to see if there was a significant improvement in the scores of the students’ writing performance from the first three blog entries to the last three blog entries. To test the second research question, a survey method was utilized. Students were provided with a questionnaire adapted from a study conducted by Aljumah (2012). Cronbach’s alpha analysis was conducted and the score was 0.897 which showed high reliability. The data analysis showed a significant improvement in all aspects of writing performance except for the aspect on voice. The mean mastery score for content on the first three blog entries (M=2.29) was significantly different from the mean mastery score of the last three blog entries (M=3.00). The mean mastery score for the first three blog entries on organization was M=2.71 which is significantly different from the mean mastery score of the last three blog entries for organization (M=3.15). The mean mastery score for the first three blog entries for sentence construction was M=2.68 and the mean mastery score for the last three blog entries was M=3.06. However, there was no significant difference in the mean mastery score for the first three blog entries on voice (M=2.68) compared to the mean mastery score for the last three blog entries (M=2.91). A significant difference was found on the final aspect of writing performance on proofreading and mechanics. The mean mastery score for the first three blog entries was M=2.09 and the last three blog entries M=2.41. On students’ perception of using weblogs in writing classrooms, the secondary school students revealed that they had enjoyed using weblogs as it helped them improve their content and sentence construction. They preferred blogging to the traditional method of writing on paper as they are able to add pictures to make their articles more interesting. However, students did mention disadvantages of using the weblogs and many of them agreed that technical problems hampered their writing process. As a conclusion, the study found that using weblogs improved students’ writing performance in terms of content, organization, sentence construction and mechanics and proofreading. There was no significant improvement in terms of students’ voice from the data analysis. On the second research question,students were very positive about using weblogs in their English writing classroom. Weblogs pose an informal writing environment that made students feel comfortable in expressing their thoughts and ideas.